At Home with the Jardines - Bell, Lilian, 1867-1929 (Salt Lake City, UT : Project Gutenberg, 2006)
"At Home with the Jardines" by Lilian Bell is a novel written in the early 20th century. The story revolves around the newly married couple, Faith and Aubrey Jardine, as they navigate the ups and downs of married life while setting up their first home. A central character in their domestic saga is Mary, their cook, who plays an integral role not only in their household management but also in the day-to-day emotional dynamics between the couple. The opening of the novel introduces the main character, Faith, as she reflects on the harmonious yet contrasting temperament between her husband, whom she affectionately refers to as "the Angel," and herself. Mary, the cook, is characterized as a formidable force within their domestic space, embodying a blend of competence, humor, and unyielding principles. As Faith details their first encounter with Mary during their honeymoon, readers get a glimpse into the vibrant personality of this character and her influence on the Jardines' lives. The dynamics between the couple and Mary lay the groundwork for both comedic and poignant moments in their journey as they settle into the complexities of married life. (This is an automatically generated summary.)
Release date is 2006-07-22
E-text prepared by Al Haines
Keywords: Domestic fiction; Married people -- Fiction